2015 30th IEEE/ACM International Conference on Automated Software Engineering (ASE) 2015
DOI: 10.1109/ase.2015.83
|View full text |Cite
|
Sign up to set email alerts
|

Synergizing Specification Miners through Model Fissions and Fusions (T)

Abstract: Software systems are often developed and released without formal specifications. For those systems that are formally specified, developers have to continuously maintain and update the specifications or have them fall out of date. To deal with the absence of formal specifications, researchers have proposed techniques to infer the missing specifications of an implementation in a variety of forms, such as finite state automaton (FSA). Despite the progress in this area, the efficacy of the proposed specification m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…APE uses Synoptic [9] to convert observed execution traces into a finite state machine (FSM) model of the target's behavior. (While APE could instead use other model-inference algorithms [6], [7], [8], [20], [23], [25], [32], [37], [39], [40], [41], [42], [43], [48], our experience showed that Synoptic model's enforcement of observed temporal invariants leads to sufficiently precise models for APE's purposes.) Each path through the FSM model represents an execution, in terms of the sequence of messages sent and received by APE.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…APE uses Synoptic [9] to convert observed execution traces into a finite state machine (FSM) model of the target's behavior. (While APE could instead use other model-inference algorithms [6], [7], [8], [20], [23], [25], [32], [37], [39], [40], [41], [42], [43], [48], our experience showed that Synoptic model's enforcement of observed temporal invariants leads to sufficiently precise models for APE's purposes.) Each path through the FSM model represents an execution, in terms of the sequence of messages sent and received by APE.…”
Section: Introductionmentioning
confidence: 79%
“…APE uses predictive model inference to abstract the observed executions into a concise and predictive model. In general, inferring the most concise model from observed examples is NP-complete [1], [17], [26], and most modelinference algorithms approximate a solution [6], [7], [8], [9], [10], [15], [20], [22], [23], [25], [31], [32], [34], [37], [39], [42], [47], [49].…”
Section: Rq1: How Quickly Does Ape Find Vulnerabilities In Tracker?mentioning
confidence: 99%
“…Also, Rahman et al [55] used static bug-finding to improve the performance of statistical defect prediction (and vice versa). Le et al [34] proposed SpecForge that combines different automaton based specification miners using model fission and model fusion in order to create a more effective specification miner. Kellogg et al [32] presents N-Prog that combines static bug detection and test case generation to avoid unnecessary human effort.…”
Section: Other Related Studiesmentioning
confidence: 99%
“…Also, our approach requires complete specifications in order to completely ensure the soundness of generated patches. We expect that employing advances in specification inference and mining could help reduce this burden [10]. Future work would be to use the history of bug fixes to mine specifications of past patches and inform the future patch generation process in a way that generated patches are likely to conform to desired behaviours.…”
Section: Preliminary Evaluationmentioning
confidence: 99%